Application-driven innovations in nanodevices for next-generation transistors, neuromorphic computing, neural interface and quantum computing - Hu, Youfan (Frontiers in Nanotechnology, 2025)
The demand for aggressive scaling in integrated circuits technology has been a primary driving force behind the rapid advancement of nanotechnology, leading to groundbreaking innovations in nanoscience, engineering, and technology. Initially, the unique phenomena observed at nanoscale enable innovative applications in nanodevices. Now, as our understanding has greatly developed, nanodevices are increasingly being leveraged to provide solutions for a growing range of applications. In this perspective, several key areas are featured that are proposed to benefit significantly from advancements in nanodevices.